Pesticide Usage in Northern Ireland : Survey Report 294 : Northern Ireland Edible Protected Crops 2019 : A National Statistics Publication.: Survey Report 294 : Northern Ireland Edible Protected Crops 2019 : A National Statistics Publication. (2020) - Lavery, M. K; Jess, J; Kirbas, D; Matthews, D; Northern Ireland., Department of Agriculture, Environment and Rural Affairs
No abstract available